2014
DOI: 10.1158/0008-5472.can-13-1400
|View full text |Cite
|
Sign up to set email alerts
|

hSETD1A Regulates Wnt Target Genes and Controls Tumor Growth of Colorectal Cancer Cells

Abstract: hSETD1A is a member of the trithorax (TrxG) family of histone methyltransferases (HMT) that methylate H3K4 at promoters of active genes. Although misregulation of mixed lineage leukemia (MLL) family proteins has been associated with acute leukemia, the role of hSETD1A in cancer remains unknown. In this study, we report that hSETD1A and its associated H3K4me3 are upregulated in human colorectal cancer cells and patient samples. Depletion of hSETD1A inhibits colorectal cancer cell growth, colony formation, and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 34 publications
5
83
1
Order By: Relevance
“…hSETD1A mainly catalyzes H3K4me3 and is thus an important coactivator of gene transcription (27). We previously showed that H3K4me3 and hSETD1A are both upregulated in colorectal cancer cell lines and primary colorectal tumors (26). We also documented that hSETD1A positively impacts the transcription of Wnt/b-catenin target genes, such as MMP7 in colorectal cancer (26).…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…hSETD1A mainly catalyzes H3K4me3 and is thus an important coactivator of gene transcription (27). We previously showed that H3K4me3 and hSETD1A are both upregulated in colorectal cancer cell lines and primary colorectal tumors (26). We also documented that hSETD1A positively impacts the transcription of Wnt/b-catenin target genes, such as MMP7 in colorectal cancer (26).…”
Section: Introductionmentioning
confidence: 83%
“…We previously showed that H3K4me3 and hSETD1A are both upregulated in colorectal cancer cell lines and primary colorectal tumors (26). We also documented that hSETD1A positively impacts the transcription of Wnt/b-catenin target genes, such as MMP7 in colorectal cancer (26). MMPs are endopeptidases critical in promoting tumor invasiveness by degrading extracellular matrix proteins, including collagens, elastins, gelatin, matrix glycoproteins, and proteoglycans (33).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations